Compressive Behaviour and Energy Absorption of Copper Tube under Quasi Static and Ultrasonic Compression Test / Nur Amanina Damira Muhalim...[et al.] - Muhalim, Nur Amanina Damira; Md Daud, Mohd Yusof; Hassan, Mohamad Zaki; Abdul Aziz, Sa’ardin; Abdul Raman, Norazmein; Sarip, Shamsul (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The application of ultrasonic vibration in metal forming has significantly reduced the forming force. This force reduction can be explained by the softening effect of material and the reduction of friction between the interfaces. However, studies on metal forming focused on the deformation of bulk metal, but specific study focusing on the application of ultrasonic vibration on tube forming is very limited. Therefore, the present study aims to investigate the compressive behavior and energy absorption of a copper tube under quasi static and ultrasonic compression. This investigation was carried out for copper tube specimens on a simple compression test set up using a constant cross head speed of 30 mm/min on dry surface condition. For the quasi static compression test, specimens were statically compressed without ultrasonic vibration between an upper and lower rigid platen. For the ultrasonic compression test, specimens were compressed with ultrasonic vibration between upper rigid platen and ultrasonic horn. A specifically designed ultrasonic horn was fabricated prior to the test as a medium to transmit the ultrasonic vibration to the specimens. The horn was tuned to a longitudinal mode at 19.89 kHz frequency with a uniform nominal vibration peak amplitude of 6 μm on the horn surface. Load displacement distributions for quasi static and ultrasonic compression tests were analysed. A comparison of quasi static and ultrasonic compression test results has been made. It was found that the compressive stress was remarkably reduced with the onset of superimposed ultrasonic vibration during plastic deformation and has lowered the energy absorption of the specimens. In addition, better deformation profiles of end products were obtained by the increase of compressibility and formability of the specimens as compared to quasi static compression.